Investigation of DPYD, MTHFR and TYMS polymorphisms on 5-fluorouracil related toxicities in colorectal cancer - Cevik, Mehtap; Namal, Esat; Sener, Nur Dinc; Koksal, Ulkuhan Iner; Cagatay, Penbe; Deliorman, Gokce; Ciftci, Cavlan; Karaalp, Atila; Susleyici, Belgin (Personalized medicine, 2022)
Aim: To investigate the association of DPYD, MTHFR and TYMS polymorphisms on 5-fluorouracil (5-FU) related toxicities and patient survival. Materials & methods: A total of 103 colorectal cancer patients prescribed 5-FU were included in the study. Genotyping was conducted for several DPYD, MTHFR and TYMS polymorphisms using a microarray analyzer. Results: DPYD 496A>G polymorphism was found to be significantly associated with 5-FU related grade 0-2, but not severe toxicities (p = 0.02). Furthermore, patients with DPYD 85TC and CC genotypes had longer progression and overall survival times compared to TT genotypes in our study group (log rank = 6.60; p = 0.01 and log rank = 4.40; p = 0.04, respectively). Conclusion: According to our results, DPYD 496AG and GG genotypes might be protective against severe adverse events compared to the AA genotype. Another DPYD polymorphism, 85T>C, may be useful in colorectal cancer prognosis. Further studies for both polymorphisms should be conducted in larger populations to achieve accurate results.Aim: To investigate the association of DPYD, MTHFR and TYMS polymorphisms on 5-fluorouracil (5-FU) related toxicities and patient survival. Materials & methods: A total of 103 colorectal cancer patients prescribed 5-FU were included in the study. Genotyping was conducted for several DPYD, MTHFR and TYMS polymorphisms using a microarray analyzer. Results: DPYD 496A>G polymorphism was found to be significantly associated with 5-FU related grade 0-2, but not severe toxicities (p = 0.02). Furthermore, patients with DPYD 85TC and CC genotypes had longer progression and overall survival times compared to TT genotypes in our study group (log rank = 6.60; p = 0.01 and log rank = 4.40; p = 0.04, respectively). Conclusion: According to our results, DPYD 496AG and GG genotypes might be protective against severe adverse events compared to the AA genotype. Another DPYD polymorphism, 85T>C, may be useful in colorectal cancer prognosis. Further studies for both polymorphisms should be conducted in larger populations to achieve accurate results.